Wildfire Smoke and Private Provision of Public Air-Quality Monitoring - Michael Coury; Liam Falconer; Andrea La Nauze (Center for Economic Studies and ifo Institute (CESifo), 2024)
Governments monitor air quality for regulatory purposes and, more recently, to provide information so individuals can act to lower their exposure to air pollution. Recent developments in low-cost technologies have also led to private adoption of air-quality monitors that produce publicly accessible air-quality readings. We study the adoption of these private air-quality monitors. We find that shocks to air pollution from wildfire result in substantial adoption. We also find that additional private monitors are concentrated in white, wealthy, and politically liberal neighborhoods. In contrast, there is no evidence that pollution shocks lead to higher adoption in neighborhoods with lower pre-existing access to monitors, higher long-run pollution, or those with more vulnerable populations. The resulting stark differences in the availability of localized air-quality information suggest that private provision may worsen not ameliorate inequalities in the impacts of poor air quality.
Keywords: Q53; Q52; 330; air quality; air quality monitoring; wildfire; information